Documenting Australia's 2019/2020 bushfires. (1st November 2020) - Main, George; Middleton, Craig; Sear, Martha; Stewart, Libby
ABSTRACT: Vast, and unprecedented, bushfires swept across the Australian continent in 2019/2020 signalling a traumatic transition into the Anthropocene. As global heating and other dimensions of this new epoch transform our physical and emotional environments, how might museums empower people to face, accept and respond to the great emotional, cultural and technical challenges of our times? Framed within the museum's broader thinking about the Anthropocene and imminent redevelopment of its environmental history gallery, this paper reflects on challenges and opportunities in the process of connecting with Australian communities to document the 2019/2020 bushfire season. It includes discussions of the acquisition of the Bungendore Firies' Fridge and the community engagement work that surrounds the acquisition of a payphone – the only public payphone in the town of Cobargo in regional New South Wales – that was charred by the deadly fires. Museums, we argue, can and often do provide important spaces to collectively acknowledge and honour the material, ecological and social connectivities that hold our communities together and thereby empower people to respond with dedication.